The efficiency of Nextera XT tagmentation depends on G and C bases in the binding motif leading to uneven coverage in bacterial species with low and neutral GC-content - Segerman, Bo; Ástvaldsson, Ásgeir; Mustafa, Linda; Skarin, Joakim; Skarin, Hanna (Frontiers in Microbiology, 2022)
Whole genome sequencing (WGS) is becoming the new standard for bacterial high-resolution typing and the performance of laboratories is being evaluated in interlaboratory comparisons. The use of the Illumina Nextera XT library preparation kit has been found to be associated with poorer performance due to a GC-content dependent coverage bias. The bias is especially strong when sequencing low GC-content species. Here we have made an in-depth analysis of the Nextera XT coverage bias problem using data from a proficiency test of the low GC-content species Campylobacter jejuni. We have compared Nextera XT with Nextera Flex/DNA Prep and examined the consequences on downstream WGS analysis when using different quantities of raw data. We have also analyzed how the coverage bias relates to differential usage of tagmentation cleavage sites. We found that the tagmentation site was characterized by a symmetrical motif with a central AT-rich region surrounded by Gs and Cs. The Gs and Cs appeared to be the main determinant for cleavage efficiency and the genomic regions that were associated with low coverage only contained low efficiency cleavage sites. This explains why low GC-content genomes and regions are more subjected to coverage bias. We furthermore extended our analysis to other datasets representing other bacterial species. We visualized how the coverage bias was large in low GC-content species such as C. jejuni, C. coli, Staphylococcus aureus and Listeria monocytogenes whereas species with neutral GC-content such as Salmonella enterica and Escherichia coli were only affected in certain regions. Species with high GC-content such as Mycobacterium tuberculosis and Pseudomonas aeruginosa were hardly affected at all. The coverage bias associated with Nextera XT was not found when Nextera Flex/DNA Prep had been used.